Teori Pembelajaran Islami: Pandangan Al-Ghazali - Milawati (Pendidikan Al-Gafari, 2025)
This research examines Al-Ghazali's views regarding Islamic learning theory and its application in modern education. Al-Ghazali, an 11th century Muslim scholar and philosopher, emphasized the importance of integrating intellectual and spiritual knowledge in the learning process. This study analyzes the principles of education and learning proposed by Al-Ghazali through his main works, such as